2017
DOI: 10.1177/0885328217722041
|View full text |Cite
|
Sign up to set email alerts
|

Construction of functional pancreatic artificial islet tissue composed of fibroblast-modified polylactic-co-glycolic acid membrane and pancreatic stem cells

Abstract: Objective To improve the biocompatibility between polylactic- co-glycolic acid membrane and pancreatic stem cells, rat fibroblasts were used to modify the polylactic- co-glycolic acid membrane. Meanwhile, we constructed artificial islet tissue by compound culturing the pancreatic stem cells and the fibroblast-modified polylactic- co-glycolic acid membrane and explored the function of artificial islets in diabetic nude mice. Methods Pancreatic stem cells were cultured on the fibroblast-modified polylactic- co-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our studies demonstrated that the fibroblasts and the ECM secreted by fibroblast scan effectively improve the biocompatibility of PLGA membrane and pancreatic stem cells, and promote the affinity between pancreatic stem cells and the PLGA membrane scaffold [15]. The pancreatic stem cells grown on the fibroblast-modified PLGA membrane can be induced to differentiate into insulin secreting cells by the two-step induction method, the PLGA artificial islet tissue containing ECM of fibroblasts and insulin secreting cells can secrete insulin and reduce blood glucose within a short term in diabetic nude mice [15]. Fibroblast-modified PLGA membrane plays a mechanical support role in the process of artificial islet tissue formation; however, non-specific inflammatory response is the main cause in primary non-function of islet transplantation [15].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our studies demonstrated that the fibroblasts and the ECM secreted by fibroblast scan effectively improve the biocompatibility of PLGA membrane and pancreatic stem cells, and promote the affinity between pancreatic stem cells and the PLGA membrane scaffold [15]. The pancreatic stem cells grown on the fibroblast-modified PLGA membrane can be induced to differentiate into insulin secreting cells by the two-step induction method, the PLGA artificial islet tissue containing ECM of fibroblasts and insulin secreting cells can secrete insulin and reduce blood glucose within a short term in diabetic nude mice [15]. Fibroblast-modified PLGA membrane plays a mechanical support role in the process of artificial islet tissue formation; however, non-specific inflammatory response is the main cause in primary non-function of islet transplantation [15].…”
Section: Discussionmentioning
confidence: 74%
“…The pancreatic stem cells grown on the fibroblast-modified PLGA membrane can be induced to differentiate into insulin secreting cells by the two-step induction method, the PLGA artificial islet tissue containing ECM of fibroblasts and insulin secreting cells can secrete insulin and reduce blood glucose within a short term in diabetic nude mice [15]. Fibroblast-modified PLGA membrane plays a mechanical support role in the process of artificial islet tissue formation; however, non-specific inflammatory response is the main cause in primary non-function of islet transplantation [15]. Hence, the research on artificial islet tissue derived from non-antigenic autologous stem cells will have a profound effect on the treatment of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffold size, mechanical stability, and diffusion distances affect the choice further. Among the in vivo studies included (n = 91) the ISC/scaffold construct was transplanted into subcutaneous locations (n = 31), 27,51,69,9294,112,115,120,133,135,145,147,156,157,171,212225 the peritoneal cavity (n = 19), 18,26,56,63,6568,101,134,135,173,195,226232 an omental pouch (n = 14), 57,59,81,118,119,163,174,225,233238 the renal capsule (n = 18), 54,…”
Section: Resultsmentioning
confidence: 99%
“…The modified PLGA membrane showed higher compatibility, improved proliferation, and increased viability of pancreatic stem cells compared with the unmodified membrane. Also, it had an enhanced histocompatibility with nude mice [112].…”
Section: Polylactic-co-glycolic Acidmentioning
confidence: 99%